Development and applications of liquid chromatography-mass spectrometry for simultaneous analysis of anti-malarial drugs in pharmaceutical formulations - Boonta Chutvirasakul (2022)
The objective of this work was to develop a high-performance liquid chromatographic method coupled with a mass spectrometer (LC–MS) for the simultaneous analysis of artemisinin-based drugs (e.g. artemisinin, dihydroartemisinin, artesunate, artemether) and piperaquine in formulations. Simultaneous separation of the investigated drugs was achieved in 14 min on a C18 column (2.1 mm x 100 mm, particle size 1.8 μm) using a gradient elution of 0.05 % v/v formic acid in water and acetonitrile. MS detection was done in a positive ionization mode using electrospray ionization with acquisition in a single ion monitoring mode. Proper diluent and storage time in an autosampler played significant roles on the quantitation accuracy since the target analytes possessed varied solubility and stability in aqueous and organic solvents. The method was fully validated according to ICH guideline and data showed good linearity (R > 0.999, precision (RSD < 3.89 %) and accuracy (%recovery between 98.5 and 103.7) with low limits of detection (LOD < 24.7 ng/mL) and quantitation (LOQ < 82.40 ng/mL). Validation data indicated that the developed LC–MS method is fit for the intended purpose and was successfully applied to evaluate the drug contents in formulations. Among the tested samples, the percent labeled amounts found were between 93.1 and 105.0 % and one supplement capsule contained 0.039 %w/w of artemisinin. The newly developed method could benefit both the quality control departments in pharmaceutical industries and the authorities working on falsified drug problems since official methods for the analysis of these drugs are not available in pharmacopoeias. The method is fast and environmentally friendly due to the requirement of less chemicals and production of less wastes.